2020
DOI: 10.15296/ijwhr.2020.64
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Low Back Pain in Primiparous Women Visiting Maternity Hospitals During Different Months of Pregnancy

Abstract: Objectives: Pregnancy is one of the pleasant periods of a woman’s life that turns into a bitter experience by common complications such as low back pain (LBP). Due to prevailing climatic conditions in Iran and the harmful social norms concerning Iranian women, the present study aimed to investigate the prevalence of pregnancy-related LBP and its influencing factors during different months of pregnancy. Materials and Methods: This descriptive cross-sectional study was conducted in 2019 on 550 pregnant women for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…After removing duplicates, the titles and abstracts of 1232 records were screened. Finally, 111 full‐text articles were assessed for eligibility, among which, 38 studies 5 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 were included in the meta‐analysis. A flow diagram of the study selection process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After removing duplicates, the titles and abstracts of 1232 records were screened. Finally, 111 full‐text articles were assessed for eligibility, among which, 38 studies 5 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 were included in the meta‐analysis. A flow diagram of the study selection process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Of these included studies, 12 studies 17 , 19 , 21 , 25 , 27 , 31 , 32 , 37 , 39 , 42 , 43 , 51 were from Asia (Malaysia, Iran, Pakistan, India, Kuwait, Nepal and China), 15 studies 18 , 22 , 28 , 29 , 33 , 35 , 36 , 38 , 40 , 44 , 47 , 48 , 49 , 50 , 52 from Europe (Turkey, Poland, Portugal, Sweden, Netherlands, Spain, UK and Norway), six studies 20 , 23 , 24 , 34 , 41 , 45 from Africa (Malawi, Nigeria and Ethiopia), four studies 5 , 30 , 44 , 53 from North America (USA), one study 26 from South America (Brazil) and two studies 46 , 50 from Oceania (Australia). The present study is was a multicenter cross‐sectional study of four countries, USA, UK, Norway and Sweden.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation